Efficacy and Safety Profile of SGLT-2 Inhibitors as Add-on Therapy in Patients with Type 2 Diabetes: A Comprehensive Review - Syed Afzal Uddin Biyabani; Neelkantreddy Patil; Syed Raziuddin Faisal (RGUHS Journal of Pharmaceutical Sciences)
This study was conducted to evaluate the efficacy and safety profile of Sodium-glucose co-transporter 2 SGLT-2 inhibitors as adjunctive therapy in patients with Type 2 diabetes. The aim was to assess their therapeutic benefits and potential risks when used in combination with standard treatment options. This study is significant because SGLT-2 inhibitors are widely prescribed and understanding their comprehensive effects is essential for optimizing patient outcomes. Several databases including PubMed the Cochrane Library Scopus Web of Science and Google Scholar were used to do a thorough literature search. All results have been analyzed based on inclusion and exclusion criteria and their findings were displayed statistically to ensure accurate comparisons between treatment groups. The management of Type 2 diabetes has shown SGLT 2 inhibitors to be highly effective increasing glycemic control lowering blood pressure promoting weight loss and having positive cardiovascular effects. A study in Korean patients reported a decrease in HbA1c by 0.68 over 12 weeks with greater reductions in the add-on group. The EMPA-REG OUTCOME trial indicated that Empagliflozin lowered HbA1c and decreased cardiovascular death by 38. SGLT-2 inhibitors also led to meaningful weight loss in 45.6 of patients. Blood pressure reduction was significant with a meta-analysis showing a drop in systolic BP by 5.04 mmHg. Empagliflozin and Canagliflozin have been shown to provide renal protection slowing the progression of kidney disease by 30. However there are safety concerns such as an increased risk of genital infections urinary tract infections diabetic ketoacidosis and a higher likelihood of fractures especially with Canagliflozin. Ongoing research is required to fully evaluate the long-term risks and benefits.